Ephesians an expositional commentary - Boice, James Montgomery, 1938-2000 (Grand Rapids, MI Baker, 1997)
Includes bibliographical references and indexes.
Donated by Doug Wilson, student at Emmaus Bible College, 1996-98.
Keywords: Bible. N.T. Ephesians -- commentaries